PENINGKATAN MOTIVASI DAN AKTIVITAS BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE WORD SQUARE PADA MATA PELAJARAN BIOLOGI KELAS X - Darmawati ' '; Irda Sayuti '; Nurhasanah ' ' (Biogenesis, 2014)
Action research has been done to improve student motivation and learning activitiesin the subjects of biology class X.3 SMAN 1 Siak Hulu using Cooperative LearningModel Type Word Square. The research was conducted in October and November2013. The subjects were X.3 grade students of SMA Negeri 1 Siak Hulu AcademicYear 2013/2014, amounting to 30 people consisting of 14 sons and 16 daughters.Parameters measured were student motivation and learning activities. The resultsshowed increased student motivation. Before the action the average studentmotivation is 2.92 (medium category), the first cycle increased to 4.21 (highcategory). In the second cycle students 'motivation has increased by an average of4.56 students' motivation (high category). The average percentage of student learningactivities showed an increase, in the first cycle category with a sufficient percentageof 66.95 % and the second cycle includes both categories with an average percentageof 84.45 %. From the results of this study indicate that learning through CooperativeLearning Model of Word Type Square can increase student motivation and learningactivities in the subjects of biology classes at SMAN X.3 1 Siak Hulu Academic Year2013/2014.Keywords: learning activities, cooperative, learning motivation, learning, wordsquare